2017
DOI: 10.1371/journal.pone.0179503
|View full text |Cite
|
Sign up to set email alerts
|

Increased inspiratory resistance affects the dynamic relationship between blood pressure changes and subarachnoid space width oscillations

Abstract: Background and objectiveRespiration is known to affect cerebrospinal fluid (CSF) movement. We hypothesised that increased inspiratory resistance would affect the dynamic relationship between blood pressure (BP) changes and subarachnoid space width (SAS) oscillations.MethodsExperiments were performed in a group of 20 healthy volunteers undergoing controlled intermittent Mueller Manoeuvres (the key characteristic of the procedure is that a studied person is subjected to a controlled, increased inspiratory resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 43 publications
2
8
0
Order By: Relevance
“…However, strong dynamic changes in the pressure of the CSF are affected mainly through venous channels. 77) Wszedybyl-Winklewska et al 78) showed that increased inspiratory resistance is associated with large swings in the heart-generated dynamic relationship between blood pressure and subarachnoid oscillations in healthy subjects. In particular, if CSF motion reaches a far distance due to respiratory fluctuations, it would indicate that such movements greatly impact substance mobilization, and this would be an essential study that gives significance to the relationship between respiration and CSF motion.…”
Section: Analysis Of Csf Motion In the Ventricular Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…However, strong dynamic changes in the pressure of the CSF are affected mainly through venous channels. 77) Wszedybyl-Winklewska et al 78) showed that increased inspiratory resistance is associated with large swings in the heart-generated dynamic relationship between blood pressure and subarachnoid oscillations in healthy subjects. In particular, if CSF motion reaches a far distance due to respiratory fluctuations, it would indicate that such movements greatly impact substance mobilization, and this would be an essential study that gives significance to the relationship between respiration and CSF motion.…”
Section: Analysis Of Csf Motion In the Ventricular Systemmentioning
confidence: 99%
“…In particular, if CSF motion reaches a far distance due to respiratory fluctuations, it would indicate that such movements greatly impact substance mobilization, and this would be an essential study that gives significance to the relationship between respiration and CSF motion. 78) All these studies concern the frequency analysis of CSF motion that started around 2015, and future developments and progress are anticipated.…”
Section: Analysis Of Csf Motion In the Ventricular Systemmentioning
confidence: 99%
“…The respiratory effort against collapsed airways during OSA apneic episodes (Mueller maneuver) is associated with elevated intrathoracic and intracranial pressures, and hemodynamic disturbances [176,177]. These have been hypothesized to acutely and repetitively impede the circulation of brain metabolites from ISF into CSF [178], through the glymphatic system, leading to increased Aβ 42 accumulation in the ISF.…”
Section: Osa Is Associated With Decreased Csf-isf Clearancementioning
confidence: 99%
“…The difference between the heart and the diaphragm is that the myocardium moves the CRF faster while the diaphragm moves a larger quantity of fluid [ 31 ]. During inhalation, thoracic pressure is reduced, which affects the subarachnoid space through the venous plexus that surrounds the thoracic spine and inside the spinal canal; the decreased thoracic pressure influences the hydrostatic pressure that helps in low venous resistance and paravenous and CRF drainage [ 32 ]. The CRF protects the functions of the central nervous system (CNS), bringing nutrients, collecting metabolic cellular wastes, and regulating cerebral pressure.…”
Section: Reviewmentioning
confidence: 99%
“…There is some evidence suggesting a reduction in the amount of CRF in motion, if there is a resistance in the respiratory tract or apnea, with a decrease in the subarachnoid space [ 32 , 34 ]. Currently, it is not known what happens with physiotherapic, osteopathic, or manual treatments of the dysfunctional inspiratory muscle and the effect they have on CRF and improving brain function.…”
Section: Reviewmentioning
confidence: 99%